GESTÃO PATRIMONIAL: UMA PROPOSTA PARA O CONTROLE DOS BENS PERMANENTES MÓVEIS INSERVÍVEIS EM UMA INSTITUIÇÃO DE ENSINO FEDERAL - Salvador, Carla (2019)
Asset management comprises a set of activities that begins with the acquisition of permanent material and ends when it is withdrawn from the institution's assets. A great difficulty of asset management occurs when the good is no lo